Bottom‑up citizen initiatives in natural hazard management: Why they appear and what they can do?. Issue 94 (April 2019) - Thaler, Thomas; Seebauer, Sebastian
Highlights: The formation of citizen initiatives remains an unguided and unpredictable process. Citizens are open to becoming involved in natural hazard management. Initiatives compensate for perceived injustice and institutional gaps. Existing social and personal capabilities support formation of initiatives. Initiatives may trigger reorientation in power sharing. Abstract: In the face of increasingly frequent and severe extreme weather events due to climate change, merely top-down governance approaches are increasingly found inadequate and ineffective. Recent climate change adaptation policy strives to promote bottom-up, citizen-driven initiatives to improve local resilience. How and under what conditions citizens may engage in collective action remains unclear, however. We employ a mixed-methods approach in Eastern Tyrol, Austria, combining stakeholder workshops with a survey of 216 citizens at risk. Results show that bottom-up citizen initiatives can provide multiple benefits, such as increasing risk awareness and local adaptive capacities. While citizens are open-minded to assuming a broad range of activities and responsibilities, local stakeholders in natural hazard management prefer to limit civic engagement to support roles, mostly during recovery from a natural hazard event. Citizen initiatives tend to emerge in communities with weak institutional capital. This may lead to conflicts with existing institutions over allocation of competences and power. Contrastingly, social and human forms of capital support the formation of initiatives; however, low willingness of citizens to assume leadership positions may be a bottleneck for sustained initiatives. Public administration and emergency organisations should address current institutional barriers. They should empower and allow citizens to act autonomously.